The effects of regional scientific opportunities in science-technology flows: Evidence from scientific literature cited in firms' patent data - Daniel Coronado; Manuel Acosta (European Regional Science Association (ERSA), 2003)
From a spatial perspective, it is well known in the literature on innovation and technological change that scientific research undertaken in the universities plays an important role as an instrument for stimulating economic growth. In general, the analysis of particular spaces, such as high technology districts or regional systems of innovation, has shown, by means of a descriptive methodology, the relevance of scientific research as a driver of regional development. With the application of spatial econometric methods, important contributions have also been made in clarifying the spillover effects of university activities. However, quantitative research on these aspects in regional contexts is still very limited. The objective of this study is to advance, from a quantitative point of view, in the knowledge of the science-technology flows from a regional perspective. We set out to answer the following kinds of question: How are science-technology flows distributed regionally? Which sectors of industry are the most dynamic in their employment of scientific knowledge? Which are the scientific fields that are most closely associated with regional industry? What factors influence the regional variability of science-technology flows' How does regional expenditure on scientific research affect science-technology flows' The methodology utilised in this study is based on the scientific citations in patent documents (NPC), and has previously only been applied in national contexts. In other words, we assume that the NPC citations, or the scientific citations, are an adequate measurement of the science-technology flows in regional contexts, too. After describing the spatial and sectorial patterns, we propose to identify the explanatory factors by modelling the citations in patent documents (taking this variable as a proxy for the science-technology flows) in function of a set of three blocks of explanatory factors: businesses (microeconomic variables), industries (sectorial variables) and spatial contexts (variables of location and of the scientific environment). The model is of the microeconomic type and the most appropriate formulation, given the nature of the endogenous variable, is that of the counted data type. The statistical data originate from a comprehensive review of the 1,643 patents applied for by 1,129 companies, and published during the years 1998 to 2001, both inclusive. The basic source of data is the domestic patent documents themselves, published by the Spanish Office of Patents and Trade Marks. This information has been tabulated to obtain regional indicators of science-technology flows and the variables for inclusion in the model. The statistical treatment of the primary information and the operation of the model provide us with objective data that may serve as an additional point of reference for reflecting on the incidence on the regional productive system of specific measures taken under regional scientific policies.
Keywords: 330